Clinical-epidemiological profile of patients with Covid-19 treated at a peruvian jungle hospital 2020: Perfil clínico y epidemiológico en pacientes Covid-19 atendidos en un hospital de la selva peruana 2020 - Becerra Uriarte, Geyner Y. (2022)
Introduction: The epidemic that had its beginning in the city of Wuhan in December 2019, has become a public health problem that is advancing at dizzying steps. Objective: To determine the clinical and epidemiological profile in Covid-19 patients attended at the Hospital Apoyo I Santiago Apóstol - Utcubamba, 2020.  Method: The type of research was observational, descriptive and retrospective cross-sectional. The population consisted of 312 patients from which a sample of 173 patients was extracted that met the conditions of being representative and adequate. All data processing and statistical calculations were performed using Microsoft Excel 2019 software. Results: Regarding the results, it was determined that the epidemiological profile: male gender a total of 102 and female gender 71, representing 59.0% and 41.0% respectively; average age of 45 years; most affected place of origin, the city of Bagua Grande, with a frequency of 162, which represents 93.6%. Regarding the clinical profile: diabetes mellitus presented a total of 7 cases, representing 4.1%; cardiovascular diseases with a frequency of 6, representing 3.5%; general malaise with a total of 75 cases, representing 43.4%; fever with a frequency of 66 cases, representing 38.2%; cough with a frequency of 56 cases, representing 32.4%; headaches with a frequency of 50 cases, representing 28.9%; and dyspnea with a frequency of 34, representing 19.7%. Conclusion: The male gender was predominant with comorbidities such as diabetes mellitus, general malaise and elevated CRP.